2011
DOI: 10.1021/je101077v
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria of Long-Chain Carboxylic Acids in Supercritical Propane

Abstract: This paper presents data on the phase behavior of long-chain acids (octanoic acid, decanoic acid, dodecanoic acid, hexadecanoic acid, octadecanoic acid, and docosanoic acid) in supercritical propane. The data were measured for acid mass fractions w acid = (0.0149 to 0.652) in the temperature range T = (375 to 412) K, and the phase transition occurred at pressures in the range p = (3.7 to 11.2) MPa. The data showed no temperature inversions yet does hint toward possible three-phase regions at low temperatures f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…A previous study has shown that, in supercritical propane, the behaviors of n -carboxylic acids systems are approximately similar to the binary phase behavior of a propane + n -alkane system where the n -alkane has double the carbon number of the n -carboxylic acid. This was explained by the dimerization effect observed for n -carboxylic acids, where two acids hydrogen bond in such a way that a “double molecule” is formed.…”
Section: Discussion Of Phase Behavior Trendsmentioning
confidence: 86%
“…A previous study has shown that, in supercritical propane, the behaviors of n -carboxylic acids systems are approximately similar to the binary phase behavior of a propane + n -alkane system where the n -alkane has double the carbon number of the n -carboxylic acid. This was explained by the dimerization effect observed for n -carboxylic acids, where two acids hydrogen bond in such a way that a “double molecule” is formed.…”
Section: Discussion Of Phase Behavior Trendsmentioning
confidence: 86%